Unveiling the diversity of macrobenthic crustaceans on sandy beaches of the eastern Mexican coast: new records and an updated checklist - María R. Muciño-Reyes; María R. Muciño-Reyes; Edlin Guerra-Castro; Edlin Guerra-Castro; Raúl E. Castillo-Cupul; Carlos E. Paz-Ríos; Nuno Simões; Nuno Simões; Nuno Simões (Frontiers in Marine Science)
Despite the ecological importance of sandy beaches, the diversity and distribution of macrocrustacean communities in the eastern Mexican coast (Mexican coast of the Gulf of Mexico and Caribbean Sea) remain understudied. As the first large-scale sampling effort along the eastern Mexican coast, this study aimed to estimate macrocrustacean diversity and evaluate sampling methodologies, while providing historical context for macrocrustacean research in the region. Two sampling designs using sediment cores (4 versus 6 cores per transect) were implemented across 15 sandy beaches. A total of 3,352 organisms were collected, representing 22 species from 17 genera, spanning 14 families, 7 suborders, 5 orders, and 2 superorders. Amphipoda and Isopoda exhibited the highest species richness and abundance. The study yielded seven new geographical records (Haustorius jayneae, Rhepoxynius epistomus, Americorchestia salomani, Heterodina mosaica, Cassidinidea ovalis, Exosphaeroma diminutum, and Sphaeroma walkeri). Results demonstrated that the 6-core sampling design provided better diversity representation. An updated checklist comprising 77 species/taxa for the eastern Mexican coast was compiled, integrating historical and new data. This comprehensive assessment enhances our understanding of these vulnerable ecosystems and emphasizes the need for broader temporal and spatial scale studies to inform effective conservation strategies.